Pengaruh Saluran Distribusi Dan Harga Terhadap Keputusan Pembelian Produk Air Cleo - M. Ajis Susilo; Syariefful Ikhwan; Slamet Bambang Riono (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
This research was conducted to discuss the influence of distribution channels and prices on Cleo's water purchase decision at PT Sentralsari Primasentosa (Ciledug Depot). The variables of this study are distribution channels (X1) and Price (X2) to purchasing decisions (Y). This research uses a type of survey research, with quantitative methods. Data analysis is assisted by the SPSS program application. The population of this study was cleo consumers with a total of 954 (stores/customers) in Brebes County. The technique of determining the number of samples, using the Slovin formula, obtained a sample of 100 respondents. Data collection techniques by distributing questionnaires to consumers. The data were then analyzed validity and reliability tests, determination tests, classical assumption tests, multiple linear regression tests, F tests and t tests. Based on the results of this study, it shows that distribution channels and prices affect cleo's water purchase decision at PT Sentralsari Primasentosa.